Memórias de quebradeiras de coco de coquelândia-ma: - ALMEIDA, Wesley de OLiveira. (Universidade Federal do Tocantins, 2024)
This dissertation seeks to give voice to the silenced and to allow the Quebradeiras de Coco group, agroextractivist women who live in the North and Northeast of Brazil, to be heard and to tell their versions about the history of the village of Coquelândia-MA. In addition to empowering the women babassu nut breakers, this work seeks, through participant research and oral history research, to develop strategies in the execution of the didactic sequence with the students of the Dorgival Pinheiro de Sousa Education Center, grandchildren of the women babassu nut breakers, to acquire historical awareness and to value their place of residence. Two methodologies were chosen in this dissertation to carry out the investigation satisfactorily; thus, we followed Thompson (2002) and Pimenta (2005) who point out that both methods complement each other by giving a place for the invisibilized to speak and contribute to the educational practice. The scholars Rüsen, Bittencourt, Nadai, Fonseca, Freire, Trompson, etc. have contributed to support the argument of this dissertation.